Correction: Exploring self-experience practices in dementia care: A scoping review. - Janina Wittmann; Anja Bieber; Joanne Carroll; Kealan Forristal; Louise Hopper; Niels Janssen; Gabriele Meyer; Marianna Riello; Marjolein de Vugt; Dorothee Bauernschmidt (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0302929.].